Madonny Polskie [arkusz znaczków podziemnych] . Polish Madonnas. Sheet of unofficial stamps - Poczta Solidarności - Fundusz Oporu Solidarność. (Poczta Solidarności)
Black and red print on golden paper, with perforation Sheet, with "Poczta Solidarności" imprint, consists of 6 stamps which represent different images of Virgin Mary, with a caption in red frame asking for a prayer. Price range: 45-75 zł per stamp.